Delineation of Upper Crustal Structure Beneath the Island of Lombok, Indonesia, Using Ambient Seismic Noise Tomography - Sarjan, Achmad F. N.; Zulfakriza, Zulfakriza; Nugraha, Andri D.; Rosalia, Shindy; Wei, Shengji; Widiyantoro, Sri; Cummins, Phil R.; Muzli, Muzli; Sahara, David P.; Puspito, Nanang T.; Priyono, Awali; Afif, Haunan (Frontiers in Earth Science, 2021)
We have successfully conducted the first ambient noise tomography on the island of Lombok, Indonesia using local waveform data observed at 20 temporary stations. Ambient noise tomography was used to delineate the seismic velocity structure in the upper crust. The waveform data were recorded from August 3rd to September 9th, 2018, using short-period and broadband sensors. There are 185 Rayleigh waves retrieved from cross-correlating the vertical components of the seismograms. We used frequency-time analysis (FTAN) to acquire the interstation group velocity from the dispersion curves. Group velocity was obtained for the period range of 1 s to 6 s. The group velocity maps were generated using the subspace inversion method and Fast Marching Method (FMM) to trace the ray-path of the surface waves through a heterogeneous medium. To extract the shear wave velocity (Vs) from the Rayleigh wave group velocity maps, we utilize the Neighborhood Algorithm (NA) method. The 2-D tomographic maps provide good resolution in the center and eastern parts of Lombok. The tomograms show prominent features with a low shear velocity appears up to 4 km depth beneath Rinjani Volcano, Northern Lombok, and Eastern Lombok. We suggest these low velocity anomalies are associated with Quaternary volcanic products, including the Holocene pyroclastic deposits of Samalas Volcano (the ancient Rinjani Volcano) which erupted in 1257. The northeast of Rinjani Volcano is characterized by higher Vs, and we suggest this may be due to the presence of igneous intrusive rock at depth.